Effect of different chemicals in reducing fruit cracking and improving yield and quality in Pomegranate cv. Pearl - Ikhlaq, Muhammad; Bashir, Muhammad Azhar; Noreen, Ammara; Shabir, Kashif; Raza, Muhammad Kashif; Bazmi, Muhammad Sultan Ali; Khalid, Naeem; Manan, Abdul (Journal of Pure and Applied Agriculture, 2023)
Pomegranate is a drought tolerant fruit crop and is well adopted to temperate to tropical climate. Fruit cracking is a major disorder in pomegranate which causes significant monetary losses. In the present study, effect of anti-biotic (T1: Streptomycin @ 1 g/L), bio-stimulant (T2: Isabion @ 1 ml/L) and fungicide Nativo (T3: Tebuconazole + Trifloxystrobin @ 1 g/L) alone or in combination of the three i.e., Streptomycin + Isabion (T4), Streptomycin + Nativo (T5), Isabion + Nativo (T6) and taking untreated plants as control (T7) were applied to minimize fruit cracking disorder in Pomegranate fruit cv. Pearl. Application of treatments started two months after fruit setting in May and repeated twice during June and July every year. Spray of these chemicals influenced productivity and fruit quality parameters of Pomegranate cv. Pearl. From mean of two years data, maximum yield per plant (51.5 kg), number of fruits per plant (243), fruit weight (252 g), number of arils per fruit (504), fruit size (55 cm2 ), total soluble solids (14.5 oBrix), juice percentage (40.6%) as well as minimum number of cracked fruit (13.8), fruit cracking percentage (5.7%) and fruit acidity (0.32%) were recorded when pomegranate plants were sprayed with Streptomycin plus Nativo (each @ 1 g/L) at monthly interval from May to July. Hence, combined application of Streptomycin and Nativo could be recommended for reducing fruit cracking and improving yield and fruit quality of Pomegranate cv. Pearl in the semi-arid climate of South Punjab, Pakistan. © 2021 Department of Agricultural Sciences, AIOU